EP222/#606 Acid ceramidase (ASAH1) expression is associated with improved overall survival in patients with high-grade serous ovarian cancer from the ICON-7 trial. (4th December 2022) - Hanker, Lars; El-Balat, Ahmed; Karn, Thomas; Holtrich, Uwe; Decker, Benedikt; Pfisterer, Jacobus; Gevensleben, Heide; Kommoss, Stefan
Abstract : Objectives: Despite recent progress in the treatment of epithelial ovarian cancer the cure of this disease remains a challenge. Therefore new treatment options along with new prognostic and predictive makers are urgently needed. The enzyme acid ceramidase (AC) plays a central role in the sphingolipid network which is involved in tumorigenesis and progression. Furthermore AC directed therapies are currently under development. We investigated the expression of AC and its prognostic impact on ovarian cancers. Methods: Patients of the AGO-cohort of the ICON-7 trial were analysed. In this randomized trial patients with advanced EOC received carboplatin+paclitaxel vs. carboplatin+paclitaxel+bevacizumab. Tissue micro arrays (TMAs) were constructed for performing immunohistochemical analysis of AC. The results were correlated with clinico-pathological characteristics and survival data. Results: Kaplan-Meier analysis (n=351) revealed that high levels of AC were associated with improved progression-free survival (PFS; 24.12 months [95% confidence interval (CI): 19.36 – 28.86] vs. 16.69 months [95% CI: 14.91 – 18.71], p < 0.0001) and overall-survival (OS; 66.83 months [95%CI: –] vs. 44.12 months [95%CI: 37.37 – 50.87], p < 0.0001). Subsequently, the prognostic value of AC expression together with clinical factors (i.e. FIGO stage, grading, histological subtype, bevacizumab medication and residual tumour burden after surgery) was further confirmed in multivariate Cox regression analysis in n= 426 patients (PFS: hazard ratio (HR) = 0.69 [95% CI: 0.550 – 0.877], p = 0.002; OS: HR = 0.67 [95%CI: 0.504 – 0.881], p = 0.004). Conclusions: Our data identify high levels of AC expression as a strong favorable prognostic marker in ovarian cancer patients.